Prevalence of, and barriers to the disclosure of HIV status to infected children and adolescents in a district of Ghana - Eric Gyamfi; Paul Okyere; Acheampong Enoch; Emmanuel Appiah-Brempong (BMC, 2017)
Abstract Background Globally there are about 3.3million children under the age of 15 years living with HIV. Of this number, 88% live in sub-Saharan Africa. In Ghana, an estimated 33,000 children were said to be living with the HIV infection in 2012. Lack of disclosure adversely affects the well-being of the child, including access to paediatric HIV treatment and care and adherence to treatment. However, the greatest psychosocial challenges that parents and caregivers of HIV-infected children face is disclosure of HIV status to their infected children. This study sought to determine the prevalence of and the barriers to the disclosure of HIV status to infected children and adolescents in Lower Manya-Krobo District in Ghana. Methods A cross sectional study with a sample of 118 caregivers of HIV infected children and adolescents aged 4-19 years attending three HIV clinics in the Lower Manya Krobo District, and 10 key informants comprising of healthcare workers and HIV volunteer workers involved in the provision of care to infected children and their families. Results The prevalence of disclosure was higher. Main barriers to disclosure identified in this study included age of child, perceived cause of HIV, stigma attached to HIV, child's inability to keep diagnosis to self and fear of psychological harm to child. Conclusion There is the need for the Ghana Health Service in conjunction with the Ghana Aids Commission and the National Aids Control Programme to develop comprehensive context-based disclosure guidelines.